Determinants of improved chickpea variety adoption in high barind region of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2020)
Chickpea production in Bangladesh has been decreasing over time. Comprehensive farmlevel adoption of modern chickpea varieties can change the scenario. This paper endeavours to ascertain the determinants of adoption and adoption intensity of improved chickpea variety in the high barind region of Bangladesh. The outcomes from Cragg’s double hurdle model showed that organization membership, information sources, crop diversification index, and village location are the crucial factors that positively influenced both the adoption and adoption level. Farmers with organization membership are 15.5% more probable to adopt improved chickpea while by adding one more information source, the adoption probability can be increased by 6.3%. Meanwhile, women’s decisions, training, credit accessibility, and farm size have effects only in favour of initial adoption. The adoption probability is approximately 15% more in the household where women can participate in the decision-making process. Adopters with higher formal education, off-farm income, and mobile usage capability devote a greater proportion of their land to the improved variety cultivation. Strengthen of the network among farmers and their information sources should be emphasized to stimulate the diffusion process of the improved chickpea variety. Besides, training should be available for both female and male of the farm families since women also affect the adoption decision.Int. J. Agril. Res. Innov. Tech. 10(1): 56-63, June 2020